Conceptualizing resource integration as an embedded process: Matching, resourcing and valuing - Caridà, Angela; Edvardsson, Bo; Colurcio, Maria (Marketing theory, 2019)
The strong linkage between the creation of value and the actors’ resource-integrating efforts forces academics and practitioners to understand how value stems from resource integration (RI). This article analyses RI as an embedded process within the wider process of interactive value formation. The study is conceptual in nature and adopts a qualitative research approach and an empirical contextualization strategy. It provides a granular perspective on RI and proposes a framework that depicts RI as a process that shapes and results from a complex service context through a sequence of three phases: matching, resourcing and valuing. The article, particularly the suggested new framework, contributes to the extant literature on RI in service research; it reconceptualizes RI as process per se that is embedded in actors’ value co-creation efforts and offers the opportunity to reflect on this process as a fundamental enabler in value-creating service ecosystems.